Industry 4.0 – An Introduction in the phenomenon - Zezulka, F.; Marcon, P.; Vesely, I.; Sajdl, O. (IFAC-PapersOnLine, 2016)
The goal of the paper is to introduce specialists from industry into the important phenomenon of the recent technology and to explain cyber – physical and informatics background of the platform Industry 4.0 and basic steps in any design and implementation of the Industry 4.0 systems. Authors introduce readers in both the RAMI 4.0 as well as the Industry 4.0 Components models which represent necessary initial background of any Industry 4.0 application. The main stress is given to the Industry 4.0 components model, which enables designers from firms to understand already existing Industry 4.0 case studies and to develop their first Industry 4.0 case studies applications.